The genus Hylaeamys (Weksler, Percequillo and Voss, 2006): species definition and phylogeny of the forest clade of Oryzomyini tribe - Brennand, Pamella Gusmão de Góes (2015)
Current patterns of faunal diversity, geographic distribution, phylogenetic relationships and biogeography constitute a tool for understanding the evolutionary history of taxa. The boundaries of these taxa and their phylogenetic relationships reveal speciation events and therefore allow us to raise general hypotheses about the diversification of a particular group. Into the Oryzomyini, one of the most diverse tribe of Sigmodontinae subfamily, we can found the genus Hylaeamys. Currently seven species were described to that genus: H. acritus, H. seuanezi, H. megacephalus, H. oniscus, H. perenensis, H. tatei and H. yunganus. These species are distributed throughout the tropical and subtropical evergreen cis-andinean forests, from sea level to an altitude of 1500 meters, from Venezuela and Guyana, through the Amazon and the Atlantic Forest, to the north of Paraguay. The distribution of taxa within the genus were confusing and phylogenetic relationships among these species have been little explored, as well as the positioning of the genus within the clade B of Oryzomyini tribe and consequently his sister group. So my proposal was to reassess the species currently described through morphometric and molecular data to better explore the diversity within the genus, and the relations within the genus Hylaeamys and clade where it is inserted. My results showed a greater diversity than the currently described. Morphometric analysis could be helpful in the delimitation of taxa, however did not translate all the phylogenetic diversity found within the genus, witch may present cryptic species. The genus is monophiletic and a new species of Hylaeamys related to H. yunganus populations, from eastern South America was recognized. The results, also highlighted a geographical structure present within H. megacephalus, so, samples from north of the Rio Amazonas showed to be genetically distinct to those samples in southern of Rio Amazon. But this pattern was not observed in morphometric analysis. The species of the Atlantic Forest were closer to the western amazonian species. Hylaeamys showed as a sister group of a clade containing Cis and Trans Andean genera: Oecomys, Euryoryzomys and Transandinomys, indicating that the dispersion for trans-Andean areas occurred after the diversification of the Forest clade in South America.